The CIPK23 protein kinase represses SLAC1‐type anion channels in Arabidopsis guard cells and stimulates stomatal opening. Issue 1 (27th January 2023) - Huang, Shouguang; Maierhofer, Tobias; Hashimoto, Kenji; Xu, Xiangyu; Karimi, Sohail M.; Müller, Heike; Geringer, Michael A.; Wang, Yi; Kudla, Jörg; De Smet, Ive; Hedrich, Rainer; Geiger, Dietmar; et al.
Summary: Guard cells control the opening of stomatal pores in the leaf surface, with the use of a network of protein kinases and phosphatases. Loss of function of the CBL‐interacting protein kinase 23 (CIPK23) was previously shown to decrease the stomatal conductance, but the molecular mechanisms underlying this response still need to be clarified. CIPK23 was specifically expressed in Arabidopsis guard cells, using an estrogen‐inducible system. Stomatal movements were linked to changes in ion channel activity, determined with double‐barreled intracellular electrodes in guard cells and with the two‐electrode voltage clamp technique in Xenopus oocytes. Expression of the phosphomimetic variant CIPK23 T190D enhanced stomatal opening, while the natural CIPK23 and a kinase‐inactive CIPK23 K60N variant did not affect stomatal movements. Overexpression of CIPK23 T190D repressed the activity of S‐type anion channels, while their steady‐state activity was unchanged by CIPK23 and CIPK23 K60N . We suggest that CIPK23 enhances the stomatal conductance at favorable growth conditions, via the regulation of several ion transport proteins in guard cells. The inhibition of SLAC1‐type anion channels is an important facet of this response.